Bonding and Infants' Development and Quality of Life: A Study Among Mothers with Severe Mental Illnesses in Remission. Issue 3 (May 2023) - Narayan, Shweta; Kishore, M. Thomas; Satyanarayana, Veena; Bhaskarapillai, Binukumar; Desai, Geetha; Chandra, Prabha
Background: Maternal mental health has specific implications for bonding and infants' mental health. However, most of the evidence comes from mothers who are either symptomatic or did not have adequate mental health support. In this context, our objective was to explore if symptom status in mothers and bonding share any significant association with the infants' development and quality of life (QOL), in case of mothers with severe mental illnesses in remission. Methods: The study included 41 mother–infant dyads from the outpatient perinatal psychiatry services and the mother–baby unit of the current study center. Symptom status, self-reported bonding, mother–infant interactions, and infants' development and QOL were assessed with Clinical Global Impressions, Postpartum Bonding Questionnaire, Pediatric Infant-Parent Exam, Developmental Assessment Scales for Indian Infants, and Pediatric Quality of Life Scale, respectively. Results: Most mothers had a complete recovery or minimal symptoms. Nine (22%) infants had a significant developmental delay. Atypical play-based interactions were observed in nine (22%) mothers. Self-reported bonding and bonding as evinced over play-based interactions did not significantly correlate with the QOL or development of the infants. Mothers who have recovered and are functioning well reported good bonding with their infants, though objective assessment revealed specific difficulties. Symptom severity correlated with poor physical QOL in infants. Conclusion: The association between mothers' bonding and infants' mental health is domain-specific and differential than linear and robust. Infants of mothers with severe mental illnesses postpartum should be routinely monitored for mother–infant bonding, development, and quality of life.